Pseudo-heterodyne signal processing scheme for interrogation of fiber Bragg grating sensor arrays - Chatterjea, C. K.; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 1998)
An intensity-based interrogation technique for arrays of fiber bragg grating (FBG) sensors is reported. The technique is based upon each FBG forming one mirror of a Michelson interferometer. Source wavelength modulation is combined with an unbalanced interferometer to produce a carrier signal. Carrier frequencies are characteristic of the optical path length imbalance and hence grating position within the array. The intensity of the carrier signal is directly related to the optical power reflected from the grating and hence the strain applied to the grating. Strain resolution of ∼3μm/m is demonstrated with an ∼350μm/m sensor range. Multiplexing is demonstrated and techniques to extend the range are disc
Keywords: Bragg gratings; multiplexing; fibre-optic sensors; interferometry